Training Seminar on Good Lab Practice Principles for Chemistry Laboratories - Good Lab Practice Principles for Chemistry Laboratories; Jayasinghe,Subadra (Colombo Institute of chemistry, 2007)
Training Seminar
Keywords: seminar reports -- Good Lab Practice ,Principles for Chemistry Laboratories